Association between neck and shoulder pain, back pain, low back pain and body composition parameters among the Japanese general population. Issue 1 (December 2015) - Iizuka, Yoichi; Iizuka, Haku; Mieda, Tokue; Tajika, Tsuyoshi; Yamamoto, Atsushi; Ohsawa, Takashi; Sasaki, Tsuyoshi; Takagishi, Kenji
Abstract Background Neck and shoulder pain, back pain and low back pain are common symptoms in Japanese subjects, and it is important to elucidate the pathology and associated factors of these pains due to their frequency and impact on the quality of life (QOL) and activities of daily living (ADL). The purpose of the present study was to investigate whether body composition is associated with these pains. Methods We collected the data of 273 Japanese subjects regarding the presence and the visual analogue scale (VAS) of neck and shoulder pain, back pain, low back pain and body composition parameters calculated using bioelectrical impedance analysis (BIA) technology. Furthermore, we investigated the association between these pains and the body composition using statistical methods. Results According to a multivariate analysis adjusted for age and gender, lower total body water ratio was significantly associated with the presence of neck and shoulder pain at present (P  < 0.05); additionally, total body muscle mass (standardized β = −0.26, 95 % CI, −0.17 - -0.008, P  < 0.05), total body water (standardized β = −0.27, 95 % CI, −0.23 - -0.04, P  < 0.01), appendicular muscle mass (standardized β = −0.29, 95 % CI, −0.36 - -0.04, P  < 0.05), and the appendicular muscle mass index (AMI) (standardized β = −0.24, 95 % CI, −1.18 - -0.20, P <0.01) were negatively correlated with the VAS of neck and shoulder pain, whereas no body composition parameters were significantly associated with back pain, low back pain at present and any type of chronic pain. Conclusions The present study demonstrated that some body composition parameters regarding body water and body muscle were associated or correlated with the presence or intensity of neck and shoulder pain.